Assessing causal relationships between sarcopenia and nonalcoholic fatty liver disease: A bidirectional Mendelian randomization study - Zhao, Ze-Hua; Zou, Juanjuan; Huang, Xin; Fan, Yu-Chen; Wang, Kai (Frontiers in Nutrition, 2022)
Background and Aims: Sarcopenia has been demonstrated to be closely associated with nonalcoholic fatty liver disease (NAFLD). However, whether there are causal relationships between sarcopenia and NAFLD remains undetermined. Here, we aim to address the question using a two-sample bidirectional mendelian randomization (MR) analysis approach. Methods: We performed a two-sample bidirectional MR study using summary-level data from genome-wide association studies (GWAS) of the whole body lean mass (n=38,292), appendicular (arms and legs) lean mass (n=28,330), and NAFLD (1483 biopsy-proven NAFLD cases and 17781 controls). We first conducted MR analysis with five single nucleotide polymorphisms (SNPs) as genetic instruments for whole body lean mass and three SNPs as instruments for appendicular lean mass to estimate the causal effect of genetically predicted sarcopenia on the risk of NAFLD using the inverse-variance weighted (IVW) method. Then we performed reverse MR analysis with four SNPs as instruments to examine the causality of genetically predicted NAFLD with whole body lean mass and appendicular lean mass. Further sensitivity analysis was conducted to testify the reliability of the MR results. Results: Genetic predisposition to decreased whole body lean mass was not associated with NAFLD (IVW-random effects, odds ratio (OR) =1.054, 95%CI: 0.750-1.482, P=0.761). Similar results were observed using genetic instruments of appendicular lean mass (IVW-random effects, OR=0.888, 95%CI: 0.386-2.042, P=0.780). Reverse MR analysis revealed that genetically predicted NAFLD using four genetic instruments was not associated with whole body lean mass (IVW, β=-0.068, 95%CI: -0.179-0.043, P=0.229) and appendicular lean mass (IVW, β=-0.020, 95%CI: -0.092-0.051, P=0.574). MR analyses using other methods and sensitivity analysis showed consistent results. Conclusions: These results suggested no causal relationships between sarcopenia and NAFLD, indicating that sarcopenia may not be directly involved in the pathogenesis of NAFLD and vice versa.